Assessment of Visual Representation Methods of Linear Discontinuous Deformation Zones in the Right-of-Way - Magdalena Wróblewska; Marcin Grygierek (Applied Sciences, 2022)
Mining impacts on the ground surface may manifest themselves, inter alia, in the form of continuous and discontinuous deformations. Discontinuous deformations significantly deteriorate the condition of the road surface, posing a threat to the safety of use. Therefore, in mining areas, it is necessary to carry out an ongoing inspection of the condition of objects and thus determine the need and scope of their repair. The key method of assessing the scope of the surface repair needed is to observe the road surface. This article presents the results of selected measurement methods carried out near discontinuous deformation zones in the right-of-way. The use of measurements with the use of a laser profilograph allowed determining the evenness of the tested pavement. Additionally, geodetic methods were used: leveling and GPS satellite positioning, to determine the displacement of points forming the observation lines along the right-of-way. In order to identify, in detail, linear discontinuous deformations, non-ceiling photogrammetry was used with the use of an unmanned aerial vehicle. The comparison of selected methods and their advantages and disadvantages allowed for the assessment of their usefulness in visual representation zones of linear discontinuous deformations. The results of this research show the usefulness of laser profilographs, while the greatest detail of the measurement was obtained by low-ceiling photogrammetry with the use of an unmanned aerial vehicle.